The Mind of Pope Francis : Jorge Mario Bergoglio's Intellectual Journey - Borghesi, Massimo, 1951- (Book collections on Project MUSE., 2018)
A commonly held impression is that Pope Francis is a compassionate shepherd and determined leader but that he lacks the intellectual depth of his recent predecessors. Massimo Borghesi's The Mind of Pope Francis: Jorge Mario Bergoglio's Intellectual Journey dismantles that image. Borghesi recounts and analyzes, for the first time, Bergoglio's intellectual formation, exploring the philosophical, theological, and spiritual principles that support the profound vision at the heart of this pope's teaching and ministry. Central to that vision is the church as a coincidentia oppositorum, holding together what might seem to be opposing and irreconcilable realities. Among his guiding lights have been the Jesuit saints Ignatius and Peter Faber; philosophers Gaston Fessard, Romano Guardini, and Alberto Methol Ferrer; and theologians Henri de Lubac and Hans Urs von Balthasar. Recognizing how these various strands have come together to shape the mind and heart of Jorge Mario Bergoglio offers essential insights into who he is and the way he is leading the church. Notably, this groundbreaking book is informed by four interviews provided to the author, via audio recordings, by the pope himself on his own intellectual formation, major portions of which are published here for the first time. -- Provided by publisher.